WAYS TO IMPROVE THE VALUE ADDED TAX ADMINISTRATION IN UZBEKISTAN (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
In this article, the administration of taxation of value-added tax in our country is studied, and it is also connected with the improvement of value-added tax. The article analyzes the specific features of calculating the value-added tax base, some complications and problems in its determination, and focuses on issues of improving the formation of the tax base. In addition, based on the results of the changes and additions made in determining and calculating the value-added tax base, relevant conclusions were formed and recommendations were developed.